1989
DOI: 10.4315/0362-028x-52.10.727
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Quality of Tofu and Related Products in Canada

Abstract: One hundred and fifty-three samples of tofu, related products, and environmental samples comprising 346 sample units were collected from 14 manufacturers across Canada. They were analyzed for coliforms, Salmonella, Yersinia, Staphylococcus aureus, and psychrotrophs. Although S. aureus counts were generally less than 250 cells per g and Salmonella was not detected, levels of psychrotrophs exceeded 106 per g in more than 45% of finished tofu and okara samples, and levels of coliforms exceeded 103 per g in more t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Researchers of Northumbria University, U.K. and Punjab University, India found that E. coli were killed by copper leaching into the water from the brass (New Scientist 2005), the results of Noyce and others (2006) clearly demonstrate the antimicrobial properties of cast copper alloys with regard to E. coli O157, and recent studies have shown that metallic copper and copper alloys have antibacterial activity over the harmful bacterium E. coli O157:H7 (as cited in Faundez and others 2004). Similar results have been reported by Szabo and others (1989); wherein 80.0% of finished tofu samples of their study had undetectable E. coli levels. Whereas Rehberger and others (1984) reported the presence of confirmed coliforms counts of 1 × 10 3 CFU/g or greater in 67% of commercial tofu lots tested.…”
Section: Microbiological Analysissupporting
confidence: 90%
See 1 more Smart Citation
“…Researchers of Northumbria University, U.K. and Punjab University, India found that E. coli were killed by copper leaching into the water from the brass (New Scientist 2005), the results of Noyce and others (2006) clearly demonstrate the antimicrobial properties of cast copper alloys with regard to E. coli O157, and recent studies have shown that metallic copper and copper alloys have antibacterial activity over the harmful bacterium E. coli O157:H7 (as cited in Faundez and others 2004). Similar results have been reported by Szabo and others (1989); wherein 80.0% of finished tofu samples of their study had undetectable E. coli levels. Whereas Rehberger and others (1984) reported the presence of confirmed coliforms counts of 1 × 10 3 CFU/g or greater in 67% of commercial tofu lots tested.…”
Section: Microbiological Analysissupporting
confidence: 90%
“…Similarly, in commercial tofu samples tested, no coagulase positive Staphylococci were detected in any sample of the study of Rehberger and others (1984). Szabo and others (1989) have reported that 5.6% of regular tofu samples analyzed contained 25 to 250 CFU/g and 1.4% contained 250 to 2500 CFU/g of Staphylococci .…”
Section: Microbiological Analysismentioning
confidence: 80%
“…The potential of various spoilage and pathogenic micro-organisms to grow in fermenting tempeh is reported by several workers (Rusmin & KO 1974;Tanaka et al 1985;Nout et al 1987Nout et al , 1988Ashenafi & Busse 1989). A variety of micro-organisms were also isolated from market tempeh and other soybean products (Samson et al 1987;Szabo et al 1989). The microorganisms in tempeh are normally killed during frying or boiling.…”
Section: Introductionmentioning
confidence: 84%
“…Different genera of foodborne bacterial pathogens are isolated from tofu or are shown to be able to grow in the product (Kovats et al . 1984; Szabo et al . 1989).…”
Section: Introductionmentioning
confidence: 99%